Forest type and burn severity affect understory response to historic wildfires - Weimer, Kate, author; Stevens-Rumann, Camille, advisor; Rocca, Monique, committee member; Ocheltree, Troy, committee member (Colorado State University. Libraries, 2023)
The fire season of 2020 was unprecedented in the Western US. In one summer, three different fires individually broke the record of Colorado's largest wildfire. Understanding the recovery following these unprecedented events can lend insight into the compounding effects of wildfire and climate change. Reorganization of the understory community after disturbance can indicate changes in conditions not yet reflected in tree communities. Understory dynamics also affect watershed characteristics and wildlife, so knowledge about the influence of wildfire on understory plants is crucial. The purpose of this study is to determine if a trend toward thermophilization is being shown in understory vegetation following 4 different wildfires in 2020 and to compare the relative importance of burn severity, forest type, and other environmental factors on understory community composition. We found a trajectory toward thermophilization in high elevation forests that burned with high severity. We also that drivers of community composition varied by forest type. These findings help assess how wildfire is affecting plant communities in the 21st Century and highlight where future management concerns may be.